Water Quality Status Determination Using Pollution Index and WQI Methods in Kalimas River, Surabaya - Aristananda, Wibi Idho; Yuliani, Emma; Prayogo , Tri Budi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
The Kalimas River, managed by the Surabaya City Government for both eco-tourism and as a crucial water source for the Kalimas River basin residents, undergoes comprehensive examination in this study. The objectives encompass assessing water quality status, mapping its distribution, and forecasting waste discharge. Employing the Pollution Index and Water Quality Index methods, findings indicate that, according to the Polluter Index, the water quality predominantly falls within the lightly polluted category, ranging from 76.19% to 90.48%. Conversely, the NSF-WQI method portrays a more concerning picture, categorizing the Kalimas River’s water quality as heavily polluted within the same percentage range. As of 2021, the existing waste discharge stands at 0.392m3/s, serving a population of 233,563 people. Mapping results highlight a general trend of good water quality downstream, with the Upper Kalimas experiencing more compromised conditions. These revelations underscore the critical need for strategic interventions and environmentally conscious policies to address escalating pollution concerns. Ensuring the sustainability of the Kalimas River, pivotal as both a tourist attraction and vital water source, requires concerted efforts in pollution mitigation and water quality management. This study serves as a valuable foundation for informed decision-making in the pursuit of a healthier and more sustainable Kalimas River ecosystem.